Dystocia in Muntiacusmuntjak - A case report - Pravesh Kumar; Akshay Sharma; Ankit Kumar Ahuja; Alisha; Jahanvi Sharma; Pururava Sharma; Pankaj Sood (The Indian Veterinary Journal, 2024)
Dystocia, or difficult labor, is a critical reproductive challenge in various mammalian species, including the barking deer (Muntiacusmuntjak).In this case, a barking deer with a history of dystocia was presented in Teaching Veterinary Clinical Complex. The doe, displaying signs of distress and prolonged labor.The forelimb of the fawn was found hanging from the vulva.Vaginal examination revealed a dead fawn with anterior presentation with one fore limb presented in the birth canal. The mal-positioned fetus was extracted out by caesarean section.